2013
DOI: 10.5812/numonthly.9430
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways in Prostate Cancer

Abstract: ObjectivesProstate cancer is a prevalent disease with a high impact on patients’ morbidity and mortality. Despite efforts to profile prostate cancer, the genetic alterations and biological processes that correlate with disease progression remain partially elusive. The purpose of this study is to review the recent evidence relating to the initiation and progression of prostate cancer in relation to the familial correlation of the disease, the genetic aberrations resulting in prostate cancer and the new molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 106 publications
0
72
0
2
Order By: Relevance
“…Prostate cancer ranges from slowly growing, indolent intraprostatic tumors to rapidly progressive metastasizing and therapy-resistant clones (2). A considerable proportion of prostate cancers will not affect the life expectancy of patients, as suggested by investigators in a recent meta-analysis of the results of 19 autopsy studies; these investigators found that among men aged 70-79 years, tumor had been discovered in 36% of white men and 51% of African American men (3).…”
Section: Introductionmentioning
confidence: 89%
“…Prostate cancer ranges from slowly growing, indolent intraprostatic tumors to rapidly progressive metastasizing and therapy-resistant clones (2). A considerable proportion of prostate cancers will not affect the life expectancy of patients, as suggested by investigators in a recent meta-analysis of the results of 19 autopsy studies; these investigators found that among men aged 70-79 years, tumor had been discovered in 36% of white men and 51% of African American men (3).…”
Section: Introductionmentioning
confidence: 89%
“…[7][8][9][10][11] AR can promote ligand-independent prostate cancer progression by directly regulating the transcription of c-Myc, 30 which confers androgen independence. 29 As a target gene of c-Myc, 17 NDRG2 has been widely accepted as a tumor suppressor in many types of cancers, 15,21,[25][26][27] and our previous study reported a negative correlation between the expression of NDRG2 and that of c-Myc in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several mechanisms underlying castration resistance have been documented, including (a) AR mutations or amplification, (b) alterations in the balance between AR and its transcriptional co-regulators and (c) growth factors/kinases signal pathways that activate AR activity at postcastration androgen levels. [7][8][9][10][11] It is noteworthy that CRPC cells retain AR and AR-regulated gene expression in the absence of or with low levels of circulating androgens. 12 In addition, tumors that are refractory to conventional androgen deprivation therapy are susceptible to more potent androgen pathway inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The progression of prostate cancer normally goes from castration-sensitive to castration-resistant, inevitably developing highly metastatic properties (3,4). Androgen deprivation therapy (ADT) is the main therapeutic approach for patients with metastatic prostate cancer (5). Prostate cancer patients respond initially to ADT, but in later stages the tumor becomes hormone refractory and more aggressive, eventually leading to poor prognosis (5).…”
Section: Introductionmentioning
confidence: 99%
“…Androgen deprivation therapy (ADT) is the main therapeutic approach for patients with metastatic prostate cancer (5). Prostate cancer patients respond initially to ADT, but in later stages the tumor becomes hormone refractory and more aggressive, eventually leading to poor prognosis (5).…”
Section: Introductionmentioning
confidence: 99%